Policy Evaluation of Ministerial Decree No. 1589/SK-HK 0201/XII/2021 on Protected Paddy Fields Map and Its Alignment with Cimahi City's 2012-2032 Spatial Plan - Widyatmoko, Wahyu; Fasa, Achmad Saeful (International Journal of Economics Development Research (IJEDR), 2024)
Indonesia is an agricultural country with a total area of 189,241,009 hectares with amazing food security potential. The issue of land conversion is a barrier for Indonesia to achieve this potential. Therefore, the Ministry of Agrarian and Spatial Planning/National Land Agency issued Decree No. 1589/SK-HK.02.01/XII/2021 on the Determination of Protected Paddy Fields Map. The Decree of the Ministry of Agrarian and Spatial Planning/National Land Agency on Protected Paddy Fields (LSD) is applied to 8 provinces throughout Indonesia, one of which is West Java Province, so Cimahi City also has the responsibility to implement this Protected Paddy Fields (LSD) program. In achieving the objective to see the implementation of Protected Paddy Fields (LSD) in Cimahi City, researchers used land cover analysis, overlay, SWOT. Land cover analysis resulted in a time lapse from 2012 to 2022 with the initial rice field area of 591.89 Ha reduced to 323.63 Ha. The results of the LSD overlay analysis with the Spatial Pattern stated that the LSD that can be maintained is 33.03 Ha. The results of SWOT analysis of X and Y coefficients (2.33, 1.44) on SWOT analysis show that it is located in quadrant I, namely Aggressive, quadrant I provides strict direction that maintaining LSD is mandatory.